2022
DOI: 10.3390/ijerph19053025
|View full text |Cite
|
Sign up to set email alerts
|

How Does Environmentally Specific Servant Leadership Fuel Employees’ Low-Carbon Behavior? The Role of Environmental Self-Accountability and Power Distance Orientation

Abstract: Environmental problems caused by excessive carbon emissions are becoming increasingly prominent and have received heightened attention in recent years. Encouraging people to adopt low-carbon behavior to reduce carbon emissions is desirable. Based on social learning theory, we developed and tested a moderated mediation model to investigate when and how environmentally specific servant (ESS) leadership impacts employees’ low-carbon behavior (i.e., private low-carbon behavior and public low-carbon behavior). We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
4
12
0
Order By: Relevance
“…This finding validates previous literature that high power distance orientation enhances the impact of managerial leadership on employee behavior (Kwak and Shim, 2017). Xia et al (2022) in their study also confirmed the moderating role of power distance orientation in the influence of environmentally-specific servant leadership on employees' environmental self-accountability and low-carbon behavior. The potential mechanism may be as follows.…”
Section: Moderating Effect Testsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding validates previous literature that high power distance orientation enhances the impact of managerial leadership on employee behavior (Kwak and Shim, 2017). Xia et al (2022) in their study also confirmed the moderating role of power distance orientation in the influence of environmentally-specific servant leadership on employees' environmental self-accountability and low-carbon behavior. The potential mechanism may be as follows.…”
Section: Moderating Effect Testsupporting
confidence: 90%
“…Notably, heavily impacted by Confucian culture, Chinese people tend to have a higher power distance orientation than Westerners (Fu and Deshpande, 2014). The acceptance of the unequal allocation of power in institutions and organizations varies among people (Xia et al, 2022), despite the fact that China has a significant power 10.3389/fpsyg.2022.1091025 distance. The leading role of leaders to employees is influenced by employees' power distance orientation, and employees with high power distance orientation are more likely to respect and rely on leaders (Farooq et al, 2017), and therefore more likely to be influenced by leaders.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous research (Xia et al, 2022), we controlled employees' demographic variables, including age, gender, and education levels.…”
Section: Control Variablesmentioning
confidence: 99%
“…Low-carbon behavior refers to the behaviors that are helpful for building a low-carbon society such as using energy-saving appliances or turning off appliances when they are not in use ( Whitmarsh et al, 2011 ). Previous studies have found that low-carbon knowledge ( Lin and Yang, 2022 ), carbon neutrality behavioral intention ( Zhao et al, 2022 ), and low-carbon awareness ( Xia et al, 2022 ) can promote individuals’ low-carbon behavior. In this study, we argue that employees’ environmental consciousness can foster their low-carbon behavior for the following reasons:…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation